Trend analysis of acute diarrheal disease mortality in Peru and regions, 1986-2015 - Valdez Huarcaya, William (2021)
Introduction. The incidence of acute diarrheal diseases (ADD) has remained relatively constant in the last three decades, whereas mortality has decreased mainly due to oral rehydration therapy and to improvements in living conditions. However, fatality is higher in poorer countries, which it is still considered a public health problem. Objective. To analyze the ADD mortality trend in children under 5 years old in Peru and its regions, in the period 1986-2015. Methods. An observational, analytical study of trends in ADD mortality in children under 5 years old in the period 1986-2015, based on secondary data, was conducted at national and regional level through segmented regression analysis of Log-Linear models using the Joinpoint program of the National Cancer Institute of the United States. Results. Peru had a reduction in the specific ADD mortality rate (1986-1990: 243.3 and 2011-2015: 15.3). In the trend analysis although all regions showed a downward trend, only in 12 remained constant throughout the period, 9 had a stationary trend, 2 upward and in 2 the reduction slowed in the last stretch. Conclusions. At national level, ADD mortality in children under 5 years old had a downward trend, although it was not constant at different times during the 1986-2015 period. In all regions, the trend was downward until 2000, then different behaviors were observed.